Dicionário privativo - GOMES, Álvaro Cardoso (Universidade Federal do Pará, 2021)
We intend to analyze in this article how the Portuguese poet Albano structures his last book, Small Privative Dictionary, followed by A Handful of Sand, like an authentic dictionary, composing poetic entries. The method used is the poem analysis, with theoretical support, aiming to detect how this singular construction serves not only to reveal the obsessing presence of death and time, but also the means to combat them, through the cult of eroticism, Beauty and Nature.